Integrated Effect of Mineral, Organic and Bio Fertilization on the Productivity of Plastic House Tomato –A Transition Step towards Organic Farming - Ali, Prof. Dr. Nooruldeen S.; ALKhalel, Shireen M. A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
A field experiment was carried out in plastic house situated at the College of Agriculture - University of Baghdad in 2009-2010 season in a Silt Clay Loam to study the effect of mineral, organic and bio- fertilizers on the yield and fruit quality (total acidity, vitamin C and total soluble solids)of tomato plants. Treatments included four levels 0%, 25%, 50% and 100% from the recommended mineral fertilizer (600 kg N ha-1 and 250 kg P ha-1) , two levels of organic fertilizer (0, 10 Mg.ha-1 of Organic fertilizer ) and two levels of bio fertilizer( 0, 950 kg ha -1) added as side dressed before planting . Results of tomato fruit total yield indicated that, treatment of 50% mineral fertilizers + organic fertilizers + bio fertilizer gave the best values in yield of tomato and quality characteristics with no significant differences than 100% mineral fertilizers + organic fertilizers + bio fertilizer. Application of bio+organic alone can give similar yield to that of 100% NP alone. The treatment of 50% mineral fertilizers + organic fertilizers + bio fertilizer gave the best values in yield of tomato and quality characteristics with no significant differences than 100% mineral fertilizers + organic fertilizers + bio fertilizer. This confirms the importance of organic and bio-fertilizer to compensate for half of the mineral fertilizers requirements and certainly with positive consequences on economical and environmental aspects.